The Relationship between Humans and Nature: inthe Light of BorderandVineyard Names and Vineyard Paths. - Lanszkiné Széles, Gabriella (Acta Scientiarum Socialium, 2011)
The Relationship between Humans and Nature: in the Light of Border and Vineyard Names and Vineyard Paths Before the middle of the 20th century the mind of a community was decisively influenced by the all-time scene of economic, social and the geographical environment that was changed from time to time by the land shaping works of human beings. The changes on the way of thinking were followed by the same procession in the way of living. New expressions and phrasing were born. It was a natural cause of the turnings above. The population’s knowledge about nature affected the set of relationship between the villages. I do stress on the importance of the still alive oral memory. In my research I leaned on the reminiscences of all those old-age people who lived close to nature.